THE EXOTIC AND THE EXPLORER: A MULTIMODAL ANALYSIS OF IDENTITY CONSTRUCTION IN A VIETNAMESE STREET FOOD REVIEW VIDEO - Hong Lien, Nguyen (Tạp chí Khoa học Trường Đại học Sư phạm Hà Nội: Khoa học Xã hội, 2025)
This study investigates the multimodal construction of identity in food media, specifically analyzing how verbal, visual, and paralinguistic modes interact to represent identities. Focusing on the most viewed YouTube review video about Vietnamese street food, the research applies Systemic Functional Linguistics to uncover social, individual, role, and lifestyle identities based on van Leeuwen’s framework of identity (2022). Findings reveal that these multimodal elements work synergistically to create an immersive experience where the food is constructed as an exotic culinary experience in relation to its perceived otherness from mainstream norms. Concurrently, reviewers leverage these resources to manifest their own identities as professional media personalities, adventurous food explorers, and expressive critics. This dual identity construction highlights how food media not only portrays diverse cuisines but also shapes public perception within digital discourse. This study contributes to the global appreciation for Vietnamese street food, thereby providing a new academic model for multimodal analysis of food media and offering practical insights for content creators to craft more convincing and authentic portrayals that challenge cultural stereotypes.